Expression and regulation of a low density lipoprotein receptor exon 12 splice variant - Ling, I-Fang (2010)
Since low density lipoprotein receptor (LDLR) contributes to cholesterol and amyloid beta homeostasis, insights into LDLR regulation may facilitate our understanding of cardiovascular disease and Alzheimer’s disease (AD). Previously, we identified LDLR isoforms that lacked exon 12 or exons 11–12 and that are predicted to encode soluble, dominant negative, LDLR. Moreover, these isoforms were associated with rs688, an exon 12 polymorphism that was associated with LDL-cholesterol and AD risk. Here, we present evidence that while the truncated LDLR isoforms are translated in vitro, they represent < 0.1% of CSF proteins. Since these LDLR isoforms likely represent a loss of mRNA encoding functional LDLR, we then focused upon identifying intron-exon boundary and exonic splicing enhancer elements critical to splicing. Exon 12 inclusion is enhanced by altering the 5′ splice site in intron 12 towards a consensus splice donor sequence, consistent with its being a weak 5′ splice site. Additionally, of the nine evolutionarily conserved putative splicing enhancer regions within exon 12, two regions that flank rs688 were critical to exon 12 inclusion. Overall, these results suggest that LDLR splice variants represent a loss of mRNA encoding functional LDLR and provide insights into the regulatory elements critical for LDLR exon 12 splicing.